Community in mission : mission consciousness of Christian communities : a contextual missiological study - Valiamangalam, Joseph; I.S.P.C.K. (Organization) (New Delhi : Indian Society for Promoting Christian Knowledge, 2008)
On the religious moorings of Dheds as a Catholic Christian community of Kheda District, Gujarat; a study.
Revision of the author's thesis-- (Ph. D.-Vidyajyoti, Delhi, Faculty of Theology)
Includes bibliographical references (p. [282]-290) and index.
Keywords: Missions -- India -- Gujarat; Christian communities -- India -- Gujarat; Dheds -- India -- Kheda (District) -- Religion; Missions -- Theory -- History of doctrines; Kheda (India : District) -- Religion